Fishery Business Analysis (Case Study: FV. Diva Bahari at Kendari Ocean Fishing Port) - Khikmawati, Liya Tri; Mainnah, Muth; Fuadi, Firhan Aldila; Bramana, Aditya (Politeknik Kelautan dan Perikanan Karawang, 2023)
Purse seine is a type of fishing gear that has the principle of catching fish by circling a school of fish. Fish caught by purse seine include lemuru, skipjack, and tuna (pelagic fish), which have economic value. One area where the majority of fishermen use purse seines is PPS Kendari. The more fishermen use the purse seine, the more it will affect the income or feasibility of the fishing business. The feasibility status of the business can be identified by conducting a business analysis of the fishing activity. Business analysis begins with participating in a trip to one of the purse seine fishing activities at PPS Kendari in January-May 2020. Carry out business-related recording activities (business capital, maintenance, and income). After the data is obtained, a business analysis will be carried out on the profit value, profit sharing system, R/C ratio, and payback period (PP). Based on the business analysis that has been done, the total cost of fishing activities is Rp. 212,716,600.00, and the company made a profit of Rp. 1,074,353,400.00. profit-sharing system, with each share amounting to Rp. 20,270,818.87. So, it can be said that fishing using purse seines at PPS Kendari is still feasible, with a value of 6.05 and a PP of 0.61 years.